The Influence of Motivation and Self-Efficacy Towards The Students’ Entrepreneurship Interest in Muhammadiyah University of Palangkaraya - Endang Sri Suyati; Achmad Zainul Rozikin (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: The students' interest in becoming entrepreneurs is influenced by several factors, such as motivation and self-efficacy. This study aimed to determine the effect of motivation and self-efficacy on students' interest in entrepreneurship at the Muhammadiyah University of Palangkaraya. This research is included in causal associative research. There are three variables in this research, they are entrepreneurial motivation, self-efficacy, and interest in entrepreneurship. The data were taken using a questionnaire. The population of this study was 1635 students, while the sample was 327 students. The researchers used a random sampling technique to choose the sample. This study used multiple regression methods. The results of this study indicated that there was an influence between motivation and self-efficacy on entrepreneurial intentions simultaneously or partially. This study indicated that the motivation variable significantly contributed to entrepreneurial interest than the self-efficacy variable.Keywords: motivation, self-efficacy, entrepreneurship interest Pengaruh Motivasi dan Efikasi Diri Terhadap Minat Berwirausaha Mahasiswa Universitas Muhammadiyah PalangkarayaAbstrak: Ketertarikan untuk menjadi wirausahawan pada mahasiswa dipengaruhi oleh beberapa faktor, diantaranya adalah motivasi dan efikasi diri pada mahasiswa itu sendiri. Tujuan penelitian ini adalah untuk mengetahui pengaruh motivasi dan efikasi diri terhadap minat berwirausaha mahasiswa Universitas Muhammadiyah Palangkaraya. Penelitian ini termasuk dalam penelitian asosiatif kausal. Data dari ketiga variabel (motivasi berwirausaha, efikasi diri dan minat berwirausaha) diambil dengan menggunakan angket. Populasi penelitian ini sebanyak 1635 mahasiswa, sedangkan sampelnya berjumlah 327 mahasiswa. Sampel diambil menggunakan teknik random sampling. Penelitian ini menggunakan metode regresi berganda. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh antara motivasi dan efikasi diri terhadap niat berwirausaha secara simultan maupun parsial. Hasil penelitian ini juga menunjukkan bahwa variabel motivasi memiliki kontribusi terhadap minat berwirausaha yang lebih besar daripada variabel efikasi diri.Kata kunci: motivasi, efikasi diri, minat berwirausaha